Rémission d’hépatite B après traitement de l’hépatite C chez une patiente noire africaine co-infectée par les deux virus. - Kpossou, A.R. (My University, 2020)
In viral hepatitis B (HVB) - viral hepatitis C (HCV) co-infection, treatment of hepatitis C results in viral reactivation B when hepatitis B is untreated. We report here a case of HVB-HVC co-infection where treatment of HVB-HVC resulted in remission of HVB. This was a 54-year-old hypertensive and diabetic patient co-infected with HVB-HVC with cytolysis and F3 fibrosis. The viral load C was significantly high and the viral load B was low (<2000 IU/ml), so we opted to first treat the hepatitis C with direct acting antivirals for 12 weeks. This treatment made it possible to make the viral loads B and C undetectable and to normalize the aminotransferases. This observation shows that, in selected cases (low viral load B), treatment of hepatitis C may lead to remission of hepatitis B in subjects co-infected with HVB-HVC
Keywords: Co-infection hepatitis B virus-hepatitis C virus; direct acting antivirals; remission of hepatitis B